People Factors Influencing Project Success in Software Development: A Survey of Agile Development Teams in Indonesia - Rifa’ah Fadilah; Teguh Raharjo; Bob Hardian; Agus Suhanto; Rufina Fitri Anjani (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2022)
Currently, agile is one method often used in software development. However, implementing agile is not easy. Many factors can affect the successful implementation of agile software development (ASD). One of the factors that often arise is individuals/people. Previous research has proven that the people factor is one of the factors that can increase the success of ASD implementation. However, only one study focuses on the people factor that researchers in Portugal have done. Therefore, this study attempts to identify the effect of people's factors on the success of ASD in Indonesia. Respondents in this study are individuals who have or are currently using ASD. Data collection in this study used a questionnaire and validated the data using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings of this study indicate that team capability influences the success of ASD implementation, while personal characteristics, societal culture, and customer involvement have no effect. In addition, other findings personal characteristics can affect team capabilities and customer involvement.